Enhancing mechanical and structural properties of TiC inserts using microwave energy - Mohamed Ariff, Tasnim Firdaus; Thauri, Shahdura Hammad; Karim, A.N. Mustafizul (2011)
Two different compositions of Titanium Carbide (TiC) inserts consisting of 97%TiC3%Ni and 93%TiC7%Ni were synthesized using conventional sintering(CS), microwave sintering (MS) and Hot Isostatic Pressing (HIP). The influence of sintering time and sintering temperature on the mechanical and structural properties of this TiC inserts were examined. The compaction load of 103 MPa was used to produce the green samples. Different time-temperature combinations were used for each type of heat treatment. 97TiC3Ni composition produced inserts with higher density, hardness and strength compared to the 93TiC7Ni composition for all three different sintering methods. Meanwhile, hybrid microwave sintering produced TiC inserts with the highest density, hardness and strength compared to conventional sintering and HIP. Improved mechanical and structural properties were observed using microwave energy in just 10 minutes of sintering compared to 10 minutes using HIP and a total processing time of 150 minutes (30 minutes holding time) using conventional sintering.